Dental implant-supported rehabilitation on a vascular-grafted mandible: A long-term and multidisciplinary approach - de Molon, Rafael S. [UNESP]; Gabrielli, Mário F. R. [UNESP]; Margonar, Rogério; Esteves, Jônatas C.; Queiroz, Thallita P.; Gabrielli, Marisa A. C. [UNESP]; Boeck, Eloisa M.; Marcantonio, Cláudio; Marcantonio, Elcio (Jaypee Brothers Medical Publishing, 2019)
Background: Facial trauma may lead to severe fractures and loss of bone and dental structures. Depending on the magnitude of the trauma, whole segments of the jaws may be lost due to comminution, exposure of internal structures, or infection. The treatment of such lesions can be challenging, and success is often hindered by unsatisfactory esthetic, phonetic, and functional outcomes. The aim of this case report was to describe a multidisciplinary approach for implant rehabilitation in a complex case of trauma in the maxillofacial region in a young patient. Case description: A 22-year-old female patient was referred with extensive loss of soft and hard tissues in the mandible as well as loss of several teeth due to facial trauma. The patient was submitted to innumerous surgical reconstructive procedures throughout years of treatment, which included vascularized soft and hard tissue grafts, installation of dental implants, Le Fort I osteotomy for maxillary repositioning, and subsequent implant-supported prosthetic rehabilitation. Conclusion: A 24-year follow-up of comprehensive surgical and prosthodontic reconstruction of a facial injury with several fractures due to motorcycle accidents using the multidisciplinary approach was described. The multidisciplinary approach employed in this case demonstrated successful outcomes for the reconstruction of the maxillofacial region after extensive facial trauma. After six years postoperatively no complications with the rehabilitation treatment has been detected to the present date. Clinical significance: The multidisciplinary treatment planning employed was able to restore masticatory function and facial esthetics, enhancing patient quality of life and satisfaction.
Keywords: Dental implant; Le Fort osteotomy; Mandibular fractures; Maxillofacial surgery; Vascular grafting